1999
DOI: 10.1016/s0035-9203(99)90287-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal amoebiasis, giardiasis and geohelminthiases: their association with other intestinal parasites and reported intestinal symptoms

Abstract: In order to determine reported signs and symptoms that may predict an intestinal parasitic infection, 241 schoolchildren in western C&e d'Ivoire were interviewed with a simnle auestionnaire and their stool specimens were examined over several consecutive days. Special emihasis was placed on (i) assessing infections bv Entamoeba histolvticalE. disaar. Giardia duoaknalis and bv intestinal worms. (ii) lookinn for associationsU between these parasites, and '(iii) looking for associatibns between these 'parasites"a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 17 publications
5
28
1
2
Order By: Relevance
“…The leading intestinal parasite in the present study was A.lumbricoides 149(55.8%) which was found to be higher than studies conducted in the same area 39.0% of the infection rate was recorded by [27] noted 31.0% of prevalence of this roundworm in Kurram Agency, Lahore (24.4%) [28] and other countries such as Ivory Cost (38.3%) [29]. The reason might be the geography of the place or the socio economic condition of the study area and the habit of the study participants in relation to wash hands before and after touching the food.…”
Section: Discussioncontrasting
confidence: 59%
“…The leading intestinal parasite in the present study was A.lumbricoides 149(55.8%) which was found to be higher than studies conducted in the same area 39.0% of the infection rate was recorded by [27] noted 31.0% of prevalence of this roundworm in Kurram Agency, Lahore (24.4%) [28] and other countries such as Ivory Cost (38.3%) [29]. The reason might be the geography of the place or the socio economic condition of the study area and the habit of the study participants in relation to wash hands before and after touching the food.…”
Section: Discussioncontrasting
confidence: 59%
“…14,22 The survey also confirmed that hookworm, with a cumulative infection prevalence of 59.9%, is the most important geohelminth, 33 whereas infections with T. trichiura and A. lumbricoides rarely occurred.…”
Section: Discussionmentioning
confidence: 73%
“…The understanding of the terms used was assessed by focus group discussions beforehand. 22,33 General and specific questions were also asked about water-contact patterns, which were identified after discussion with community key informants and a walk through the village.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two principal factors in maintaining endemicity of intestinal helminthes infections are favorable quantities of the soil and frequent contamination of the environment by human faeces [10]. Their transmission within the community is predominantly related to human habits with regards to eating, defecation, personal hygiene, cleanliness and level of education [11]. Its prevalence in the community can be used as an indication of the conditions of living, environmental sanitation as well as the socio-economic status of the community [12].…”
Section: Introductionmentioning
confidence: 99%